Business use of the World Wide Web: a report on further investigations - Hooi-Im Ng; Ying Jie Pan; T.D. Wilson (Information Research: An International Electronic Journal)
As a continuation of a previous study this paper reports on a series of studies into business use of the World Wide Web and, more generally the Internet. The use of the World Wide Web as a business tool has increased rapidly for the past three years, and the benefits of the World Wide Web to business and customers are discussed, together with the barriers that hold back future development of electronic commerce. As with the previous study we report on a desk survey of 300 randomly selected business Web sites and on the results of an electronic mail questionnaire sent to the sample companies. An extended version of this paper has been submitted to the International Journal of Information Management